2017
DOI: 10.21608/asejaiqjsae.2017.4082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative insecticidal activity of nano and coarse silica on the Chinese beetle Callosobruchus Chinensis (L) (Coleoptera: Bruchidae)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The LT 50 values of the tested substances against 6th instar larvae of C. cephalonica revealed that MSNs were faster to act than CESNs and silica gel. A similar observation was obtained by Mesbah et al ( 2017 ), who found that silica nanoparticles were more biologically active than normal silica against the Chinese beetle Callosobruchus chinensis (Linnaeus), where the LT 50 values of the silica nanoparticles were 67.52, 72.23, and 83.44 h, which were less than those of normal silica at 120.15, 131.44, and 140.00 h.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The LT 50 values of the tested substances against 6th instar larvae of C. cephalonica revealed that MSNs were faster to act than CESNs and silica gel. A similar observation was obtained by Mesbah et al ( 2017 ), who found that silica nanoparticles were more biologically active than normal silica against the Chinese beetle Callosobruchus chinensis (Linnaeus), where the LT 50 values of the silica nanoparticles were 67.52, 72.23, and 83.44 h, which were less than those of normal silica at 120.15, 131.44, and 140.00 h.…”
Section: Resultssupporting
confidence: 86%
“…It caused a decrease in larval survival by 40% mortality at a minimum concentration of 15 mg. After 6 days of exposure, this mortality increased to 56.7, 86.7, and 96.7% at concentrations of 30, 60, and 90 mg, respectively (Table 2). The toxicity of MSNs was recorded previously against various insects (Mesbah et al 2017;Arumugam et al 2016;Ziaee and Ganji 2016; El-Samahy et al 2014;Vani and Brindhaa 2013;Barik et al 2012;Galal and El-samahy 2012;Rouhani et al 2012 andDebnath et al 2011).…”
Section: Insecticidal Activity Of Msns Cesns Eos and Silica Gel Again...mentioning
confidence: 88%